Corporate Social Responsibility Sebagai Pemediasi Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Leverage Terhadap Nilai Perusahaan - Baiq Dewi Lita Andiana (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to obtain evidence of the role of CSR in mediating the relationship between firm size, profitability and leverage with firm value. The research was conducted on companies that are members of the LQ45 index listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The method of determining the sample used is a purposive sampling technique. The number of samples obtained were 31 companies with a total of 124 observations in a 4 year time series. The analysis technique used is path analysis. The results of this study indicate that the firm size variable has a negative effect, the profitability and leverage variables have a positive effect, and the CSR variable has no effect on firm value. As for the direct influence on CSR, there are no variables that have a significant effect. Based on the results of this analysis, it is also found that CSR is not able to mediate the relationship between company size, profitability, and leverage with firm value in LQ45 index companies. The results of this research are to enrich knowledge and are used as a reference in investment and capital market courses, for management to be used as material for consideration in making improvements or enhancing company performance. As for investors, these results can be used as a reference before making investment decisions. Kata kunci: Ukuran, Profitabilitas, Leverage, CSR, Nilai